Variations upon the fantastic in Rosa Montero's short stories. Issue 2 (2015) - Squires, Jeremy
Abstract : Tzvetan Todorov's well-known definition of the fantastic is that it teeters on the boundary between two modes – the uncanny and the marvellous – creating an impression of being in two worlds at once, and of hesitating between them. However, several short stories by the contemporary writer Rosa Montero do not precisely conform to Todorov's model. Rather than hesitate, some of her characters re-enchant reality through forms of imaginary thinking which are enabling (though not always upliftingly so). Montero's characters, like experienced readers, prove capable of harnessing uncanny scenarios, thereby rendering their worlds more knowable and homely. Such reactions can be genuinely renovating and epiphanic, yet may equally be instances of bad faith. This article examines five of the author's realist short stories with fantastical trappings, two in each category ('El monstruo del lago' and 'Él'; 'Un tumulto de ahogados' and 'La otra'), and another, 'Retrato de familia', where psychology falls short of metaphysics and a more classically Todorovian sense of limbo ensues.